2003
DOI: 10.1177/0193841x03259029
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Outcomes from the Casaworks for Families Intervention for Substance-Abusing Women on Welfare

Abstract: A field evaluation with repeated measures at 6 and 12 months on an intent-to-treat sample of 529 women conducted in 11 selected sites across the country. There were significant improvements shown in substance use and family and social functioning by the 6-month point, and additional improvements in employment by the 12-month point. By 12 months, more than 46% were abstinent from alcohol and other drugs, and 30% were employed at least part-time. There were only modest improvements shown in the medical and psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…Five of these (Evenson et al, 1998;Jansson et al, 2003;Laken & Ager, 1996;Lanehart et al, 1996;McLellan et al, 2003) found that case management enhanced retention or treatment outcomes. Two other studies (Howell & Chasnoff, 1999;Marsh et al, 2000) found inconclusive or paradoxical findings regarding the effect of case management.…”
Section: Case Management And/or One-stop Shopping Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Five of these (Evenson et al, 1998;Jansson et al, 2003;Laken & Ager, 1996;Lanehart et al, 1996;McLellan et al, 2003) found that case management enhanced retention or treatment outcomes. Two other studies (Howell & Chasnoff, 1999;Marsh et al, 2000) found inconclusive or paradoxical findings regarding the effect of case management.…”
Section: Case Management And/or One-stop Shopping Modelmentioning
confidence: 99%
“…The path analysis results of Laken and Ager (1996) showed a significant association between case management service and treatment retention for pregnant women. McLellan et al (2003) showed that welfare-recipient women who participated in the CASAWORKS for Families program made significant improvements in the areas of substance abuse and social/family functioning at 6-month followup and employment at 12-month follow-up. The CASAWORKS for Families program emphasized interorganizational coordination so that women could receive comprehensive and concurrent services.…”
Section: Provision For Case Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, researchers also documented changes in related problems such as criminal recidivism, physical and mental illnesses, and employment (e.g., Brady & Ashley, 2005;Clark, 2001;Dodge & Willander, 2001;Greenfield et al, 2004;Hall et al, 2004;Hser, Evans, & Huang, 2005;Inciardi, Martin, & Butzin, 2004;McLellan et al, 2003;Peters, Haas, & Hunt, 2002;Sowers et al, 2002). Although the nature of treatment programs varies substantially (e.g., therapeutic communities, 12-step programs, residential treatment, outpatient programs), the findings on substance abuse treatment can be summed up as showing that substance abuse treatment is not 100% effective, but it is generally more effective than no treatment.…”
Section: Substance Usementioning
confidence: 99%